Postnatal growth and short-term complications in very low birth weight neonates receiving total parenteral nutrition - Purkayastha, Jayashree; Soundaram, V; Lewis, Leslie Edward; Bhat, Y Ramesh (Indian Journal of Child Health, 2016)
Objective: To study the postnatal growth and short-term complications in very low birth weight preterm neonates receiving total parenteral nutrition (TPN). Methods: This prospective, observational study was conducted in the neonatal intensive care unit of a tertiary care hospital in South India. All neonates with birth weight <1250 g and <32 weeks of gestation who received TPN and survived at least 7 days were studied prospectively. Amino acid infusion was started at 1 g/kg/day on day 1 and graded up to 4 g/kg/day. Lipids were started on the day 2 of life at 1 g/kg/day and graded up to 3 g/kg/day. Enteral feeds were introduced within 3 days of life. TPN was stopped once enteral feeds reached 100 ml/kg/day. Postnatal growth and biochemical and hematological parameters were also monitored. Results: Time to reach full enteral feeds was 11.3±4.5 days, cumulative weight loss proportion (in %) was 8.5±4.7, and number of days to regain birth weight was 11.1±4.5 days. Mean growth velocity (GV) at 30 days of life and 40 weeks of postmenstrual age (PMA) was 16.37±4.8 g/kg/day and 20.03±5.8 g/day, respectively. Mean GV of appropriate for gestational age (AGA) infants was 3.13 g/kg/day, lower compared to small for GA (SGA) infants at 30 days PMA (p=0.01). However, there was no statistical difference in GV between AGA and SGA infants at 40 weeks of PMA. There was no correlation between energy intake on the day 7 and weight and head circumference at 40 weeks of PMA. Hyponatremia was observed in 40.6% infants receiving TPN, and there were no other significant complications. Conclusion: Conventional TPN was associated with favorable postnatal growth until 30 days of postnatal life. However, catch-up growth at 40 weeks of PMA was not satisfactory. Mean GV of AGA infants was found to be lower compared to that in SGA infants at 30 days of postnatal life. Besides hyponatremia, there was no major complication due to TPN in this study.